Body politics between sublimation and subversion: critical perspectives on twentieth-century all male performances of Shakespeare's As You Like It - Baumgärtel, Stephan Arnulf (2005)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-graduação em Letras/Inglês e Literatura Correspondente.